Integrasi Kurikulum Merdeka dan Kurikulum Pesantren di Madrasah Aliyah pada Pondok Pesantren - A. Sibron; Muhammad Win Afgani; Afriantoni Afriantoni (Departement of Mathematics Education, 2024)
Education in Indonesia continues to evolve to meet the needs of the times, especially in the digital era and globalization. Pondok pesantren, as the oldest Islamic educational institution, faces the challenge of blending tradition with modernity in its curriculum. This research aims to explore the integration of the Kurikulum Merdeka and the Pesantren Curriculum in Madrasah Aliyah within pondok pesantren, focusing on enhancing digital literacy, developing the character of the Pancasila Student Profile, and addressing the shortcomings of the old curriculum. This study employs theoretical and literature analysis to evaluate the effectiveness of this curriculum integration. Teachers are given the freedom to choose teaching methods that suit the needs of students, such as the P5 project, which emphasizes critical, creative, and multilateral character skills. The results of the study indicate that the integration of the Kurikulum Merdeka and the Pesantren Curriculum creates a more adaptive educational context oriented towards Pancasila values. This integration not only enhances students' digital literacy and character but also provides space for teachers to develop innovative teaching methods. This curriculum integration is capable of addressing old shortcomings and improving teaching effectiveness, thereby meeting students' needs more holistically. Thus, this integration is expected to continue to be developed and implemented more widely to create a generation that is competent and characterized according to the Pancasila Student Profile.